Anion‐Regulated Hydroxysulfide Monoliths as OER/ORR/HER Electrocatalysts and their Applications in Self‐Powered Electrochemical Water Splitting. Issue 12 (4th May 2018) - Wang, Bin; Tang, Cheng; Wang, Hao‐Fan; Li, Bo‐Quan; Cui, Xiaoyang; Zhang, Qiang
Abstract: Trifunctional electrocatalysis for the oxygen evolution reaction, oxygen reduction reaction, and hydrogen evolution reaction constitutes the bottleneck of various sustainable energy devices and systems including rechargeable metal–air batteries and overall water splitting. Emerging macroscopically nanostructured catalysts are strongly requested for superior electrocatalytic activities and practical applications. Here, a 3D hydroxysulfide monolith with anion‐regulated NiFe hydroxysulfide nanosheets is rationally proposed. With abundant active sites and unique structure, the as‐obtained hydroxysulfide monolith exhibits superior electrocatalytic performance in oxygen evolution, hydrogen evolution, and oxygen reduction in alkaline electrolyte. When directly serving as electrodes, a small charge/discharge voltage gap of 0.76 V at 2.0 mA cm −2 and a high peak power density of 248 mW cm −2 are achieved for the liquid Zn−air batteries, and a low cell voltage of 1.62 V at 10 mA cm −2 is detected for water splitting units. When two Zn−air batteries are serially connected to power the water splitting unit, bulky O2 and H2 bubbles are continuously generated on both the composite electrodes. This work demonstrates an effective strategy for controllable anion regulation and rational design of the 3D self‐supporting hydroxysulfides, which is also enlightening for other advanced energy materials and diverse applications. Abstract : A free‐standing hydroxysulfide monolith is in situ grown on 3D conductive Ni foam scaffolds through a green room‐temperature electrodeposition and sulfurization strategy. With rationally anion‐regulated NiFe hydroxysulfides and unique structure, this composite exhibits impressive oxygen evolution reaction/hydrogen evolution reaction/oxygen reduction reaction reactivity and great performance in Zn−air batteries and overall water splitting.